Exploring the Relationship Between Unemployment Rate and Economic Growth in the Philippines - Arangel Dua; Karen Mae R Tabigue; Karl P. Campos (Universitas YARSI, 2025)
This study examines the relationship between unemployment and economic growth, controlling for government expenditure, inflation, population growth, and investment. Using time series techniques such as the Augmented Dickey-Fuller test, Johansen cointegration, Vector Error Correction Models (VECM), and Granger causality tests, the analysis reveals that unemployment does not have a significant short-term effect on GDP growth. However, a significant long-term relationship exists, consistent with Okun’s Law, which describes an inverse connection between unemployment and economic growth. The findings suggest that while short-term fluctuations in unemployment may not immediately impact economic performance, sustained changes in unemployment influence long-term growth patterns. Additionally, government expenditure and investment play important roles in shaping economic outcomes, while inflation appears less influential in this context. The study highlights the importance of focusing on long-term labor market improvements as a key driver of economic growth and provides valuable insights for policymakers seeking to foster stable growth and employment.